Analisis Faktor-Faktor Yang Mempengaruhi Kepuasan Kerja Pada Personel Samapta Polres Penajam Paser Utara - Artika Sari, Devi; Hadiyatno, Didik; Cahyaning Putri Cipto, Rahajeng (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2025)
Job satisfaction is a crucial issue inherent in police personnel. This is because the vulnerability to danger inherent in the profession can lead to job dissatisfaction, especially Samapta officers. This study intends to examine various factors divided into work discipline, motivation, and compensation on the job satisfaction of Samapta personnel of the North Penajam Paser Police. The population in this study reached 108 Samapta personnel of the North Penajam Paser Police and the sample used was all Samapta personnel of the North Penajam Paser Police. The analysis tool used in this study was multiple linear regression with the help of smart PLS software and applying a total sampling technique where the entire population was sampled. The method of collecting data was carried out by observation, interviews and distributing questionnaires. The results of this study indicate that the variables of work discipline and motivation each have a positive and significant effect on job satisfaction. While the compensation variable does not have a significant effect on job satisfaction. The influence of the study proves that the satisfaction of police personnel is not always related to money factors, and more attention needs to be paid to fulfilling psychological needs.